The Development of Module of Malay Traditional Kueh in Johor Using Banana Leaves as Wrapper - Abdul Rahman, Abdul Wafi; Abdullah, Nur Syareeza; Md Sahak, Adibah Aishah; Mohd Yazid, Nur Diyana; Abd Rani, Afif Naim (Research and Innovation in Technical and Vocational Education and Training, 2023)
Developing a module of Malay traditional kueh in Johor using banana leaves as wrappers has helped teachers and students during the teaching and learning process. Besides, this module has become a source of reference for lecturers and students. However, the main problems are that no current reference or resources that focus on Malay traditional kueh in Johor using banana leaves as wrappers for Culinary Arts students. In addition, the absence of modules becomes a problem for both the teaching staff and students during the teaching and learning (T&L) process. Therefore, the aim of this study was to develop a module of Malay traditional kueh in Johor using banana leaves as wrappers for the instructors, teachers, and students who took the Culinary Arts course. This study uses quantitative methods in which the data is evaluated based on the average percentage of experts evaluated using an evaluation form. The development of this module aims to access the suitability of the content, format, clarity, and design of the module for the use of teachers and students in the Culinary fields during the learning process. This module has been evaluated using an experts’ evaluation form by 4 experts in Culinary Arts. Using the average percentage value, the results showed that the level of suitability in terms of content, format, clarity, and module design was at a high level which is 90% agreed. So it is confirmed that this module is suitable to use by lecturers and students, especially in the Culinary Arts fields. In conclusion, the development of learning modules for Culinary Arts students can assist lecturers and students during the same learning session as a source of reference.